An exploratory qualitative interview study on grassroots esports in sports clubs - Baumann, André C. K.; Pallesen, Ståle; Mentzoni, Rune A.; Kolberg, Eirin; Waagbø, Vegard; Sørensen, Anders; Kristensen, Joakim H. (Frontiers in Sports and Active Living, 2024)
Aim: The current study aimed to explore grassroots esports in sports clubs in Norway from the perspective of volunteer esports leaders. Method and results: Fifteen volunteers were recruited from grassroots esports initiatives in various sports clubs and were interviewed via online video conferencing using a pre-developed semi-structured interview guide. Data was analyzed using inductive thematic analysis with a realist approach, which generated the following themes: 1) Local community impact at the center of motivation, 2) lack of support threatens the operations of the initiatives, and 3) competency development to overcome barriers. The participants perceived the grassroots esports initiatives as essential for children in the local community and as the core of their motivation as volunteers. Several challenges were mentioned for sustaining the initiatives, such as maintaining motivation, resource management, and recruiting new volunteers. Finally, competency and qualified esports trainers were mentioned as necessary for a high-quality offer. Conclusion: The grassroots esports initiatives in sports clubs are viewed by volunteer esports leaders to affect the local community positively. However, there are challenges tied to the operation of such initiatives, such as engaging volunteers and raising competence. Future research should investigate barriers to help develop strategies to support grassroots esports initiatives.